Hypermethylation of Metallothionein-I Promoter and Suppression of Its Induction in Cell Lines Overexpressing the Large Subunit of Ku Protein - Majumder, Sarmila (1999)
We have shown previously that the heavy metal-induced metallothionein-I (MT-I) gene expression is specifically repressed in a rat fibroblast cell line (Ku-80) overexpressing the 80-kDa subunit of Ku autoantigen but not in cell lines overexpressing the 70-kDa subunit or Ku heterodimer. Here, we explored the molecular mechanism of silencing of MT-I gene in Ku-80 cells. Genomic footprinting analysis revealed both basal and heavy metal-inducible binding at specific cis elements in the parental cell line (Rat-1). By contrast, MT-I promoter in Ku-80 cells was refractory to any transactivating factors, implying alteration of chromatin structure. Treatment of two clonal lines of Ku-80 cells with 5-azacytidine, a potent DNA demethylating agent, rendered MT-I gene inducible by heavy metals, suggesting that the gene is methylated in these cells. Bisulfite genomic sequencing revealed that all 21 CpG dinucleotides in MT-I immediate promoter were methylated in Ku-80 cells, whereas only four CpG dinucleotides were methylated in Rat-1 cells. Almost all methylated CpG dinucleotides were demethylated in Ku-80 cells after 5-azacytidine treatment. To our knowledge, this is the first report that describes hypermethylation of a specific gene promoter and its resultant silencing in response to overexpression of a cellular protein.